Peran Istri Sebagai Pendukung Dakwah Suami Pada Film Buya Hamka Vol 1 - Mahardhika, Jibril Wahyu; Mustiawan; Setiawati, Titin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research investigates the role of the wife as a supporter of her husband's da'wah, as depicted in the film Buya Hamka Vol.1. The film portrays Siti Raham, the wife of Buya Hamka, and her contributions to her husband's missionary efforts. Employing a qualitative approach, this study utilizes content analysis to examine the portrayal of the wife's role in supporting her husband's da'wah. The analysis focuses on five specific scenes in the film that illustrate the wife's contributions. The findings identify five key roles that wives play in supporting their husband's da'wah: advisor, motivator, teacher, companion, and household manager. The results underscore the significant role wives have in providing moral, emotional, and spiritual support to their husbands, in addition to contributing to the education of their children. Furthermore, this research highlights the importance of effective communication and mutual understanding between husband and wife in ensuring the success of da'wah. These findings offer valuable insights into the dynamics of the wife's role in supporting her husband's da'wah and establish a foundation for strategies to enhance da'wah effectiveness.